Trend of trade union membership in selected countries. - Loh, Aik Mei. (2008)
The study examines the trend of trade union membership in selected countries like United States of America, United Kingdom, Germany, Australia, Japan, Singapore, Malaysia, Thailand, Philippines, and Indonesia.